ANALISIS PEMBERLAKUAN NON TARIFF MEASURES (NTM) PADA EKSPOR HORTIKULTURA INDONESIA KE ASEAN +3 - Darmiati Dahar; Rina Oktaviani; Wiwiek Rindayati (Bina Ekonomi, 2014)
This study analyzes the application of non-tariff measures (NTM) in Indonesian horticultural exports to the ASEAN +3 countries. This study is based on the use of NTM that are increasingly used by every country in the world. Sanitary and Phitosanitary (SPS) and Technical Barriers to Trade (TBT) are the most common barriers in trade. This study used descriptive analysis to describe the performance of Indonesian horticultural exports to the ASEAN +3 countries. Indonesian horticultural exports are compared with a number of NTM in the application of export destinations. The result obtained from this study is that almost all horticultural export destinations in the ASEAN +3 impose NTM in horticultural products. Singapore is a country that does implement the NTM Horticulture products, and that’s why Indonesia does export a lot to Singapore.